Detection of the Hematopoietic Stem and Progenitor Cell Marker CD133 during Angiogenesis in Three-Dimensional Collagen Gel Culture. (23rd June 2013) - Akita, Masumi; Tanaka, Kayoko; Matsumoto, Sachiko; Komatsu, Kumiko; Fujita, Keiko
Abstract : We detected the hematopoietic stem and progenitor cell marker CD133 using immunogold labeling during angiogenesis in a three-dimensional collagen gel culture. CD133-positive cells were present in capillary tubes newly formed from aortic explants in vitro. The CD133-positive cell population had the capacity to form capillary tubes. Lovastatin strongly inhibited cell migration from aortic explants and caused the degradation of the capillary tubes. The present study provides insight into the function of CD133 during angiogenesis as well as an explanation for the antiangiogenic effect of statins.